Transcriptome and co-expression network analysis reveals the molecular mechanism of inosine monophosphate-specific deposition in chicken muscle - Yu, Baojun; Cai, Zhengyun; Liu, Jiamin; Zhao, Wei; Fu, Xi; Gu, Yaling; Zhang, Juan (Frontiers in Physiology, 2023)
Inosine monophosphate (IMP) content in chicken meat is closely related to muscle quality, an important material basis that affects meat flavor. However, the molecular regulatory mechanisms of muscle IMP-specific deposition remain unclear. This study performed transcriptome analysis on muscle tissue from different parts, feeding methods, sexes, and breeds of 180-day-old Jingyuan chickens, combined with differential expression and weighted gene co-expression network analysis (WGCNA), to identify functional genes that regulate IMP deposition. 1,775, 409, 102, and 60 differentially expressed genes (DEGs) were identified in four comparison groups, in which PDHA2, ACSS2, PGAM1, GAPDH, PGM1, GPI, and TPI1 may be involved in the anabolic process of muscle IMP in the form of energy metabolism or amino acid metabolism. WGCNA identified 11 biofunctional modules related to IMP deposition. The brown, midnightblue, red, and yellow modules were strongly correlated with IMP and cooking loss (P < 0.05). Functional enrichment analysis showed that glycolysis/gluconeogenesis, arginine and proline metabolism, and pyruvate metabolism regulated by PYCR1, SMOX, and ACSS2 genes were necessary for muscle IMP-specific deposition. In addition, combined analyses of DEGs and four functional modules identified TGIF1 and THBS1 as potential candidate genes affecting muscle IMP deposition. The results elucidated the molecular mechanisms of muscle IMP deposition through key genes and signaling pathways, providing an important theoretical basis for improving meat quality and the molecular breeding of Jingyuan chickens.